2002
DOI: 10.1116/1.1491988
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange at the interfaces of mixed anion III–V heterostructures grown by molecular beam epitaxy

Abstract: High-resolution x-ray diffraction was used to characterize and compare the exchange process at the interfaces of mixed anion heterostructures. Superlattices (SLs) formed by the Sb2 exposure of As-stabilized GaAs surfaces and the As4 exposure of Sb-stabilized GaSb surfaces were grown by molecular beam epitaxy and characterized. Interface composition profiles have been determined using full dynamical simulations of the SL structures that exhibited anion exchange. Comparisons between As-for-Sb exchange on GaSb an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Dynamical simulations of X-ray spectra were used to determine the phosphorus composition present at the interfaces of the -GaAs SL structures. X-ray simulation and analysis proceeded using the Philips high resolution epitaxy simulation software to determine the composition profiles at the SL interfaces [3].…”
Section: Methodsmentioning
confidence: 99%
“…Dynamical simulations of X-ray spectra were used to determine the phosphorus composition present at the interfaces of the -GaAs SL structures. X-ray simulation and analysis proceeded using the Philips high resolution epitaxy simulation software to determine the composition profiles at the SL interfaces [3].…”
Section: Methodsmentioning
confidence: 99%
“…The rate of As for Sb exchange is sensitive to the surface composition. As the exchange reaction proceeds, the first layer Sb atoms are depleted resulting in an As enriched surface layer, which inhibits further exchange [15]. Therefore, compositional variations within the surface layer, such as regions enriched in Sb, will tend to be eliminated.…”
Section: Article In Pressmentioning
confidence: 96%
“…However, the hole localization energy was previously reported to be much smaller than theoretically predicted [1]. Subsequent work has shown that under typical molecular beam epitaxy (MBE) [2] and organometallic vapour phase epitaxy (OMVPE) [3,4] conditions, a large fraction of the deposited Sb tends to segregate to the surface when the GaSb quantum well layer is overgrown by GaAs; this leads to intermixing of the two anionic species. The Sb atoms form a floating surface layer, which is gradually depleted by its incorporation into the growing GaAs.…”
Section: Introductionmentioning
confidence: 95%